Inventory Model Simulation to Reduce Bullwhip - Mujaddid Mujaddid; Sapta Asmal; Saiful Mangngenre (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2025)
One of the issues that frequently arise in the supply chain is the bullwhip effect. The bullwhip effect is simply the presence of a distant intersection of supply and demand. To address this issue, inventory management must be implemented in order to provide products or services at the appropriate time and location. The goal of this study is to reduce the occurrence of the bullwhip effect, increase service level, and consider total cost and profit. The method used is the RQ policy. RQ policy is a fixed replenishment point inventory policy / fixed replenishment quantity policy referred to as an RQ policy. When the inventory level drops below the fixed replenishment point (R), the product's fixed replenishment quantity (Q) is ordered, which is simulated in anylogistix software to determine the optimal inventory policy and design. The optimal simulation results are R:15,000 and Q:30,000 with an inventory capacity of 30,000, a bullwhip effect value of 1.62 to 1, indicating no bullwhip effect, and a service level of 0.90 to 1, indicating that all orders can be fulfilled. with the right timing and profits ranging from Rp. 74.400.000 to Rp. 101,450,000.